2020
DOI: 10.1186/s40359-020-00417-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mindfulness-based cognitive therapy on risk and protective factors of depressive relapse – a randomized wait-list controlled trial

Abstract: Background: The aim of this randomized wait-list controlled trial was to explore the effects of Mindfulness-Based Cognitive Therapy (MBCT) on risk and protective factors for depressive relapse within the domains of cognition, emotion and self-relatedness. Methods: Sixty-eight individuals with recurrent depressive disorder were randomized to MBCT or a wait-list control condition (WLC). Results: Completers of MBCT (N = 26) improved significantly on measures assessing risk and protective factors of recurrent depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 91 publications
(103 reference statements)
0
33
0
Order By: Relevance
“…The participants also underwent electrocardiography (ECG) measurement and performed cognitive tests that are not reported in the present study. For further details regarding the details of the data collection, please see Schanche et al (2020).…”
Section: Sampling Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…The participants also underwent electrocardiography (ECG) measurement and performed cognitive tests that are not reported in the present study. For further details regarding the details of the data collection, please see Schanche et al (2020).…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…In a recent RCT of MBCT (Schanche et al, 2020), from which the data in the present study are retrieved, the main effect of MBCT was in the domain of self-relatedness, as measured by the SCS (Neff, 2003). The SCS is a composite scale that comprises both how the individual relates to themselves, whether they feel isolated or connected to others and whether they feel over-identified with own thoughts and emotions.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies have shown that Yoga therapy/meditation can improve health and well-being of a diseased individual by reducing stress besides boosting the immune response (Thirthalli et al, 2013;Danhauer et al, 2019;Tang et al, 2020;Venkatesh et al, 2020). Mindfulness-based cognitive therapy can significantly reduce stress, depression and anger, when administered in-person, or virtually (Schanche et al, 2020;Kuo et al, 2021;Orosa-Duarte et al, 2021;Strauss et al, 2021). Similar to Yoga, mindfulness-based Abbreviations: ACE2, Angiotensin-converting enzyme 2; ARDS, Acute respiratory distress syndrome; CD4, Cluster of differentiation 4; CD8, Cluster of differentiation 8; COVID-19, Coronavirus Disease 2019; COX2, Cyclooxygenase 2; HCWs, Health care workers; HDAC2, Histone Deacetylase 2; HDAC3, Histone Deacetylase 3; HDAC9, Histone Deacetylase 9; LDBT, Isha kriya or long duration breathing technique; MCP-1, Monocyte chemoattractant protein-1; RIPK2, Receptor-interacting serine/threonine-protein kinase 2; SARS, Severe Acute Respiratory Syndrome; SARS-CoV-2, Severe acute respiratory syndrome coronavirus 2/novel coronavirus; SDBT, Simha kriya or short duration breathing technique.…”
Section: Introductionmentioning
confidence: 99%